Public Consumer Protection in The Polish Insurance Market: Scope And Effects - Anna PIECHOTA; Malgorzata JEZIORSKA (Communications of International Proceedings, 2022)
The financial market encompasses the entire gamut of relationships involved in raising and distributing money, in which consumers are one of the main links. It involves a multitude of transactions and is potentially exposed to a number of irregularities, including infringements of consumer interests. Usually, consumers of financial services have little specialist knowledge, they also have limited experience and are hamstrung by information gaps. The lack of an effective framework may have a negative impact on the stability of the entire financial system. This is why promoting transparency, simplicity and fairness in the financial markets is so important. In Poland, there are numerous institutions authorized to take action with regard to irregularities in the activity of financial service providers reported by the consumer. Insurance is a very important part of the financial sector. The public institutions tasked with acting for all insurance customers are, first of all, the Financial Ombudsman (FO) and the Financial Supervision Authority (FSA). The main purpose of the article is to determine whether the irregularities in the insurance market in Poland are identified by the indicated institutions. The additional objective of the work is to identify what these irregularities involve, what areas they affect, what their scale is, and, finally, what actions are taken in response to any reported or observed irregularities. The research is based on data from requests to the FO and the reports notified to the FSA (data for 2016-2020).
Keywords: Consumer protection; insurance market; financial services